(untitled) (Marketing Journal, 2025)
This paper conducts an in -depth analysis of socio -economic differentiation across Uzbekistanʼs regions between 2018 and 2024, using the Regional Disparity Index (RDI) framework. The main objective is to measure the evolution of interregional disparities through economic, digital, and export indicators and to identify convergence tendencies across territories. The study constructs a composite index based on Gross Region al Product (GRP), employment, digital infrastructure, and export volume. Panel data regres sion and GIS -based visualization techniques were employed to assess both № 10-SON OKTA BR, 2025 -YIL 112 temporal and spatial dynamics of regional inequality. The findings reveal a gradual yet steady convergence process during the study period, although structural diversification remains uneven across provinces.